2012
DOI: 10.2174/1876525401204010020
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of 48h vs. 24h Injection of Parathyroid Hormone for Amelioration of Osteopenic Spine Properties in Male Rats

Abstract: Daily application of parathyroid hormone (PTH 1-34) is used for treatment of osteoporosis. It was investigated whether orchiectomy-induced osteoporotic changes in spine can be ameliorated by every 48h administration of PTH in aged male rats. Eight-month-old male Sprague-Dawley rats were sham operated (n=24) or orchiectomized (Orx, n=36) and maintained untreated over 12 weeks. Thereafter, both tibia underwent transverse metaphyseal osteotomy (Komrakova et al. 2011, J Endocrinol; 209:9-19) and rats were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Recent work has demonstrated that mitochondria are a preferred target of UCN. These effects were first described for cardioprotective effects of UCN (40). It was shown that death rate of myocyte cell was decreased after administration of UCN.…”
Section: Parametersmentioning
confidence: 94%
“…Recent work has demonstrated that mitochondria are a preferred target of UCN. These effects were first described for cardioprotective effects of UCN (40). It was shown that death rate of myocyte cell was decreased after administration of UCN.…”
Section: Parametersmentioning
confidence: 94%
“…For analysis of mineral content, L4 and right femur were ashed at 750°C for one hour in a muffle oven. Weight before ashing (organic) and after ashing (anorganic) were recorded ( 13 , 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…The tibia was ashed at 750°C for 1 h. Afterwards, calcium content was quantified with an atomic absorption spectrometer (4100; PerkinElmer, Baesweiler, Germany). Orthophosphate content was assessed by the colorimetric method (Spectral Photometer DM4; Zeiss, Jena, Germany) (67, 72). The inorganic weight was measured after ashing as a percentage of the wet weight before ashing (39).…”
Section: Methodsmentioning
confidence: 99%